2014
DOI: 10.1016/j.ygyno.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Credentialing of DNA methylation assays for human genes as diagnostic biomarkers of cervical intraepithelial neoplasia in high-risk HPV positive women

Abstract: ObjectiveTesting for high risk human papillomavirus (HR-HPV) is increasing; however due to limitations in specificity there remains a need for better triage tests. Research efforts have focused recently on methylation of human genes which show promise as diagnostic classifiers.MethodsMethylation of 26 genes: APC, CADM1, CCND2, CDH13, CDKN2A, CTNNB1, DAPK1, DPYS, EDNRB, EPB41L3, ESR1, GSTP1, HIN1, JAM3, LMX1, MAL, MDR1, PAX1, PTGS2, RARB, RASSF1, SLIT2, SOX1, SPARC, TERT and TWIST1 was measured by pyrosequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 35 publications
8
88
0
1
Order By: Relevance
“…The lower sensitivity in this subgroup, where detec- tion is based on methylation of EPB41L3 alone, suggested that addition of methylation assays for other hrHPV may be warranted. Among the 26 human genes originally considered for the human gene methylation component of the S4 classifier [22], EPB41L3 showed the strongest potential. However, the gene selection was based on earlier reports either describing promising QMSP assays or showing aberrant methylation by at least two different research groups.…”
Section: Discussionmentioning
confidence: 99%
“…The lower sensitivity in this subgroup, where detec- tion is based on methylation of EPB41L3 alone, suggested that addition of methylation assays for other hrHPV may be warranted. Among the 26 human genes originally considered for the human gene methylation component of the S4 classifier [22], EPB41L3 showed the strongest potential. However, the gene selection was based on earlier reports either describing promising QMSP assays or showing aberrant methylation by at least two different research groups.…”
Section: Discussionmentioning
confidence: 99%
“…Gene sites that have shown potential to be used as a diagnostic marker of cervical pre-cancer and cancer were selected for the analyses. 6,18,21 The human EPB41L3 gene, also known as What's new? Cervical cancer detection in women with human papillomavirus (HPV) infection may be aided by the identification of methylation markers in host and viral DNA.…”
Section: Methylation Assaymentioning
confidence: 99%
“…16 For EPB41L3 and LMX1A, the primers were designed using PyroMark Assay Design software version 2.0.1.15 (Qiagen). 21 The methods for amplification and pyrosequencing and the associated quality control procedures have been described in detail elsewhere. 16,18,21 …”
Section: Methylation Assaymentioning
confidence: 99%
“…A methylation signature comprising the 5 0 regions of the genes DLX1, ITGA4, RXFP3, SOX17, and ZNF671 specific for CIN3 and cervical cancer has been validated using quantitative methylationspecific PCR (24). Other investigators have separately identified EpB41L3 methylation (25) and CpG7091 methylation (26) as potential biomarkers for risk stratification and triage of women with high-risk HPV infections. Finally, in the randomized, controlled PROHTECT-3 trial, DNA methylation analysis of MAL and miR124-2 genes on HPV-positive self-samples was recently reported to be noninferior to cytology triage in the detection of CIN2 or worse, suggesting that full molecular screening should be feasible (27).…”
Section: State Of the Sciencementioning
confidence: 99%